Majlis Perbandaran Segamat / Nur Afiqa Atasha Anuar - Anuar, Nur Afiqa Atasha (Faculty of Business and Management, 2023)
This industrial training report provides an overview of the experience gained during a training program at Majlis Perbandaran Segamat (MPS). The report begins with an updated resume highlighting the skills, knowledge, and experiences gained during the training program. It also includes the company profile that describes the organization's background, functions, and objectives. The report then discusses the reflection on the training program, which includes the knowledge, skills, and experiences gained during the training. The reflection highlights the practical application of theoretical concepts, the challenges faced, and the lessons learned during the training. Furthermore, the report presents a SWOT analysis of the organization. This analysis provides insights into the company's strengths, weaknesses, opportunities, and threats. The analysis shows that the organization has strengths in terms of its competent workforce and dedicated leadership, but it also faces challenges in terms ofresource constraints. Finally, based on the analysis, the report provides recommendations to Majlis Perbandaran Segamat on how to improve its operations and achieve its goals. The recommendations include enhancing employee relationships among them, training and development programs and investing in technology and innovation. Overall, this report provides a comprehensive overview of the training experience at Majlis Perbandaran Segamat, and it provides recommendationsto help the organization improve its operations and achieve its goals